2005
DOI: 10.1097/01.prs.0000152424.91250.a5
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Microvascular Free Tissue Transfer in the Elderly Population

Abstract: The objective of this study was to evaluate the safety and thus the efficacy of microvascular free tissue transfer in the elderly patient population. Free flaps for different types of reconstructions were analyzed to verify whether free tissue transfer is feasible in the elderly. Between 1993 and 2003, 102 free flaps were performed in 94 patients who were aged 70 years or older. There were 75 male and 19 female patients, with a mean age of 73.8 years (range, 70 to 87 years). Different types of free flaps were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 18 publications
6
106
0
7
Order By: Relevance
“…In a large retrospective series examining free flap reconstruction in 100 consecutive patients over the age of 65, Serletti et al also concluded that age should not be a contraindication for free flap transfer, and that the ASA status and operative time are significant predictors of medical and surgical morbidity [11]. Chick et al and Coskunfirat et al produced similar findings in populations groups of over 65 and 70s [12,13]. Specific to octogenarians, Blackwell et al published their experience in free flap head and neck reconstruction in 13 patients and found it a reliable reconstructive method, albeit one associated with a higher likelihood of medical complications and higher associated economic cost [14].…”
Section: Discussionsupporting
confidence: 58%
“…In a large retrospective series examining free flap reconstruction in 100 consecutive patients over the age of 65, Serletti et al also concluded that age should not be a contraindication for free flap transfer, and that the ASA status and operative time are significant predictors of medical and surgical morbidity [11]. Chick et al and Coskunfirat et al produced similar findings in populations groups of over 65 and 70s [12,13]. Specific to octogenarians, Blackwell et al published their experience in free flap head and neck reconstruction in 13 patients and found it a reliable reconstructive method, albeit one associated with a higher likelihood of medical complications and higher associated economic cost [14].…”
Section: Discussionsupporting
confidence: 58%
“…The ASA scoring system was the dominant system used in the literature (2)(3)(4)(5)(6)(8)(9)(10)(12)(13)(14)(17)(18)(19)(20). Three studies calculated CCI scores (3,21,22) and only one study used the KFI (11).…”
Section: Methodsmentioning
confidence: 99%
“…Preoperative comorbidities and tools for their assessment were also investigated. Many studies agreed that these conditions are risk factors for systemic complications, but some favored the ASA classification (4)(5)(6)(8)(9)(10), some the CCI (3), and some the Kaplan Feinstein Index (KFI) (11), so there was no consensus on the method of assessment. Longer surgical duration's effect on complications and mortality is another area of debate (4,5,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronological age alone is neither a contraindication for surgery nor a risk for postoperative morbidity and flap failure 8,9 . A preoperative high ASA status is associated with higher postoperative morbidity 10,11 . Patients with head and neck cancer are often elderly, smokers, with a history of alcoholism and, therefore, associated with comorbidity (heart and lung), sometimes associated with poor nutritional status.…”
Section: Anesthetic Approach Preoperativementioning
confidence: 99%